2021
DOI: 10.24996/ijs.2021.62.8.4
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Urotensin-II Levels with Insulin Resistance and Endothelin-I in Type-II Diabetes Mellitus Patients

Abstract: Urotensin-II (UII), a pluripotent vasoactive cyclic peptide, exhibits the progression of cardiovascular diseases and the glucose metabolic disorder of insulin resistance. Type 2 Diabetes Mellitus (T2DM) is entirely associated with insulin resistance. This study aimed to demonstrate the association of UII with insulin resistance in diabetic and non-diabetic subjects. A total of 73 male and female subjects aged 40-60 years were recruited in this case-control study. They included 35 non- diabetic subjects with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Endothelin is a prominent vasoconstrictor that is synthesized and released by vascular endothelial cells, that was first found by Yanagisawa, Inoue 1,2 ET is known to have a role in leading to many cardiovascular diseases 3 . Jankowich et al 4 described the association of ET-1 with hypertension, cardiac remodeling, aging, chronic kidney disease, pulmonary hypertension and diabetes 5 . It has been demonstrated that endothelin-1 (ET-1) induces pulmonary vasoconstriction through the activation of Ras homolog family member A 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Endothelin is a prominent vasoconstrictor that is synthesized and released by vascular endothelial cells, that was first found by Yanagisawa, Inoue 1,2 ET is known to have a role in leading to many cardiovascular diseases 3 . Jankowich et al 4 described the association of ET-1 with hypertension, cardiac remodeling, aging, chronic kidney disease, pulmonary hypertension and diabetes 5 . It has been demonstrated that endothelin-1 (ET-1) induces pulmonary vasoconstriction through the activation of Ras homolog family member A 6 .…”
Section: Introductionmentioning
confidence: 99%